The Influence of Teachers' Creativity on Learning Motivation to Read the Qur'an at Madrasah Aliyah Negeri (MAN) 1 Sumbawa - Mas’un Mas’un; Fathurrahman Muhtar; Ribahan Ribahan (MANAZHIM, 2023)
Teachers are educators, mentors, coaches, and curriculum balancers who can create conditions and a conducive learning atmosphere, such as a fun, interesting learning atmosphere, giving students space to think actively and innovatively in exploring and elaborating their abilities. The teacher's role is very important in improving student learning achievement so they must be more creative in choosing teaching methods. The purpose of this study was to determine the influence of teacher creativity on motivation to learn to read the Koran in students of Madrasah Aliyah Negeri (MAN) 1 Sumbawa. This type of research is ex post facto comparative causal research using a quantitative approach. The research instrument was a questionnaire based on the research procedures used in this study. Data analysis was carried out through research instrument tests which included validity and reliability followed by the classical assumption test. The method used is multiple linear regression analysis. The results of the study show that teacher creativity has a direct effect on learning motivation. Because it has a probability value (0.000) <0.05, which means there is a positive and significant influence between teacher creativity on learning motivation. This means that the higher the teacher's creativity in teaching, the higher the learning motivation of students in class X Madarasah Aliyah Negeri (MAN) 1 Sumbawa.